Mitochondrial haplogroup R offers protection against obesity in Kuwaiti and Qatari populations - Dashti, Mohammed; Ali, Naser M.; Alsaleh, Hussain; John, Sumi Elsa; Nizam, Rasheeba; Al-Mulla, Fahd; Thanaraj, Thangavel Alphonse (Frontiers in Endocrinology, 2024)
Background: The Kuwaiti and Qatari populations have a high prevalence of obesity, a major risk factor for various metabolic disorders. Previous studies have independently explored mitochondrial DNA (mtDNA) variations and their association with obesity in these populations. This study aims to investigate the role of mtDNA haplogroups and variants in obesity risk among these Gulf populations. Methods: Whole exome sequencing data from 1,112 participants (348 Kuwaitis and 764 Qataris) were analyzed for mtDNA variants. Participants were classified as obese or non-obese based on body mass index (BMI). Association analyses were performed to examine the relationship between mtDNA haplogroups and obesity, adjusting for covariates such as age and sex. Results: Haplogroup R was found to be protective against obesity, with an odds ratio (OR) of 0.69 (p = 0.045). This association remained significant after adjusting for age and sex (OR = 0.694; 95% CI: 0.482-0.997; p = 0.048). Several mtDNA variants, particularly those involved in mitochondrial energy metabolism, showed nominal associations with obesity, but these did not remain significant after correcting for multiple testing. Conclusion: Haplogroup R consistently demonstrates a protective association against obesity in both Kuwaiti and Qatari populations, highlighting its potential as a biomarker for obesity risk in the Gulf region. However, further research with larger sample sizes is needed to validate these findings and clarify the role of mtDNA variants in obesity.